The Average Cost of Residents’ Diet in Yerevan - Beglaryan, M. R.; Markosyan, D. Z. (ՀԱԱՀ հիմնադրամ)
Food prices are important in the context of meeting humans’ basic needs including diet. Therefore, this study aims to assess the cost of the average diet in the capital of Armenia, Yerevan, where one-third of the population resides. Consumption patterns were studied using a 24-hour recall survey amongst the Yerevan population considering the age range between 18 and 65. Overall, 1264 respondents from 12 districts of Yerevan have participated in the survey. Afterwards, the average cost of per capita monthly diet was calculated and theoretically compared with the healthy diet cost reported in the literature sources.
Keywords: Agricultural Economics and Agribusiness